Design of a humanized anti vascular endothelial growth factor nanobody and evaluation of its in vitro function - Fatemeh Kazemi-Lomedasht; serge muyldermans; Mahdi Habibi-Anbouhi; Mahdi Behdani (Iranian Journal of Basic Medical Sciences, 2018)
Objective(s): Nanobodies, the single domain antigen binding fragments of heavy chain-only antibodies occurring naturally in camelid sera, are the smallest intact antigen binding entities. Their minimal size assists in reaching otherwise largely inaccessible regions of antigens. However, their camelid origin raises a possible concern of immunogenicity when used for human therapy. Humanization is a promising approach to overcome the problem.   Materials and Methods: Here, we designed a humanized version of previously developed nanobody (anti vascular endothelial growth factor nanobody), evaluated and compared its predicted 3D structure, affinity and biological activity with its original wild type nanobody. Results: Our in silico results revealed an identical 3D structure of the humanized nanobody as compare to original nanobody. In vitro studies also demonstrated that the humanization had no significant visible effect on the nanobody affinity or on its biological activity.  Conclusion: The humanized nanobody could be developed and proposed as a promising lead to target pathologic angiogenesis.